Enterprise Financing Mode and Technological Innovation Behavior Selection: An Empirical Analysis Based on the Data of the World Bank's Survey of Chinese Private Enterprises. (16th March 2021) - Zhu, Entao; Zhang, Qiming; Sun, Lan
Abstract : In China, private enterprises are becoming more and more important subjects of technological innovation, however(at the same time) financing difficulties of private enterprises are also ubiquitous. The research on the impact of financing methods on technological innovation behavior of private enterprises is conducive for the government to launch more targeted financing support policies.I men private enterprises are becoming the mainbody of technological innovation, but the difficulties in financing is especially heavy in China. Based on the data of the World Bank survey on China's enterprises in 2012, this paper studies the impact of different financing methods on technological innovation behavior of private enterprises. The results show that (1) internal financing can promote the technological innovation behavior of enterprises better than external financing can do and (2) among the various forms of external financing, bank loans have the most significant impact on the technological innovation behavior of private enterprises, followed by commercial credit.